Experiences of men with breast cancer: an exploratory focus group study - Williams, B G (Nature Publishing Group, 2003)
Management and care of men with breast cancer is based on that developed for women. Our study reports that men have specific issues regarding certain aspects of their breast cancer experience, including diagnosis, disclosure, support and gender-specific information, and offers suggestions for improved patient care.